Crystal growth in amorphous films of tantalum pentoxide - Bagmut, A. G. (My University, 2023)
Amorphous films are formed on substrates at room temperature in the process of pulsed laser sputtering of Ta target in an oxygen atmosphere. Electron beam irradiation causes their crystallization with the formation of Ta2O5 crystals with hexagonal lattice. Electron microscope investigation, including “in situ” and video recording methods, revealed the following crystallization modes in different regions of the same amorphous film of Ta2O5. 1. Island polymorphous crystallization. 2. Interjacent crystallization mode. 3. Layer polymorphous crystallization mode. The presence of three different crystallization modes is explained by the phenomenon of polyamorphism in amorphous films.
Keywords: crystallization modes; polyamorphism; relative length; tantalum pentoxide; video